Seismogenic Patches in a Tectonic Fault Interface - Ostapchuk, Aleksey; Polyatykin, Vladimir; Popov, Maxim; Kocharyan, Gevorg (Frontiers in Earth Science, 2022)
Tectonic faults show rheological heterogeneity of interfaces, and the spectrum of their sliding regimes span a continuum from slow slip events to dynamic ruptures. The heterogeneity of fault interface is crucial for the mechanics of faulting. By using earthquake source locations, the complex structure of a fault interface can be reproduced at a resolution down to 50-100 m. Here we use a declustered seismic catalogue of Northern California to investigate structures of 11 segments of San Andreas, Calaveras and Hayward faults. The cumulative length of all segments is about 500 km. All the selected segments belong to subvertical strike-slip faults. A noticeable localization of sources near fault cores is observed for all the segments. The projection of earthquake sources to fault plane shows a severe inhomogeneity. Topologically dense clusters (seismogenic patches (SPs)) can be detected in fault planes. These clusters are the more distinct, the longer are the observations. The SPs usually cover about 10-20 % of the fault interface area. It is in the vicinity of SPs that earthquake of magnitude above 5 are usually initiated. The Voronoi tessellation is used to determine the orderliness of SPs. Distributions of areas of Voronoi cells of all the SPs obey the lognormal law, and the value of Voronoi entropy of 1.6 – 1.9 prevails. Findings show the informativeness of the background seismicity to reveal the heterogeneous structure of a tectonic fault interface.